Adaptor molecules mediate negative regulation of macrophage inflammatory pathways: a closer look - Baig, Mirza S.; Barmpoutsi, Spyridoula; Bharti, Shreya; Weigert, Andreas; Hirani, Nik; Atre, Rajat; Khabiya, Rakhi; Sharma, Rahul; Sarup, Shivmuni; Savai, Rajkumar (Frontiers in Immunology, 2024)
Macrophages play a central role in initiating, maintaining and terminating inflammation. For that, macrophages respond to various external stimuli in changing environments through signaling pathways that are tightly regulated and interconnected. This process involves, among others, autoregulatory loops that activate and deactivate macrophages through various cytokines, stimulants and other chemical mediators. Adaptor proteins play an indispensable role in facilitating various inflammatory signals. These proteins are dynamic and flexible modulators of immune cell signaling and act as molecular bridges between cell surface receptors and intracellular effector molecules. They are involved in regulating physiological inflammation, but also contribute significantly to the development of chronic inflammatory processes. This is at least partly due to their involvement in the activation and deactivation of macrophages, leading to changes in the macrophages' activation/phenotype. This review provides a comprehensive overview of the 20 adaptor molecules and proteins that act as negative regulators of inflammation in macrophages and effectively suppress inflammatory signaling pathways. We emphasize the functional role of adaptors in signal transduction in macrophages and their influence on the phenotypic transition of macrophages from pro-inflammatory M1-like states to anti-inflammatory M2-like phenotypes. This endeavor mainly aims at highlighting and orchestrating the intricate dynamics of adaptor molecules by elucidating the associated key roles along with respective domains and opening avenues for therapeutic and investigative purposes in the clinical practice.